PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. NUSANTARA SURYA SAKTI PONTIANAK - B31109002, Iko Kusuma Hadi (Jurnal Manajemen Update, 2013)
Motivation is something showing up from each of individual and environment around us to get organization goal. Motivation that shows from individual (intrinsic) is success in work, admit, work for itself, respondsibility, and development. For the external motivation (Extrinsic) is salary, work environment, work relation, superiasion, and policy instansy. The purpose of this reserche is to know how motivations in work influence on PT. Nusantara Surya Sakti Pontianak. In this reserche is used primer date taken from using questioner, and than the date gets analysed by using SPSS Version 16.0 Program. By this reserche having done it brings us to the conclusion that hygiene factor or exstrinsic affect the performance of employees and motivator factor or intrinsic too affect with employees job performance. Keyword : Hygene Factor (Exstrinsic), Motivator Factor (Intrinsic), Employees Performance